Surface properties of latex film and solvent-borne film resulted from fluorinated acrylate copolymers prepared by emulsion polymerization (eXPRESS Polymer Letters)
The fluorinated acrylate copolymer, poly (BMA-co-DFHMA), was prepared by emulsion polymerization using a preemulsified monomer addition process. The FTIR and 1H –NMR were used to characterize the copolymer structure. The contact angle of water on the solvent-borne film increased dramatically and reached an equilibrium value (103°) when the PDFHMA content in the copolymer was only 0.97 mol%. However, the contact of water on the latex film increased slowly, and reached the equilibrium value of 99° until the fluorinated component content was as highly as 9 mol%. A similar result was observed for the oil contact angle on the two types of films. XPS results showed that when the F/C ratio on film surfaces reached equilibrium, the required content of fluorinated component in the copolymer for the solvent-borne film was much lower than that for the latex film.